A reforma do ensino médio pela Lei 13.415/2017: uma política de currículo de muitos nós nas threads do Twitter - Mira, Ane Patricia Viana José de (Universidade do Vale do Rio dos Sinos, 2023)
The studies on the curriculum policies of the new high school have intensified following the approval of law 13,415/17 in December 2017, which modified the National Education Guidelines and Bases Law (LDB) regarding the final stage of basic education: high school. The aforementioned law altered the high school curriculum. The terms competencies, skills, knowledge objects, and knowledge areas have become part of the discussions that permeate the actors involved in the changes. These discussions have been heated due to two important factors: the rise of the far-right in Brazil, with the election of President Jair Bolsonaro in 2018, and the unexpected arrival of the Covid-19 pandemic in December 2019. Given this scenario, the investigated topic is the reform of high school education based on Law 13,415/17, as a curriculum policy from a social justice perspective. The general objective of this study was to understand the new high school education as a curriculum policy and its implications in the social debate from a social justice perspective, on the social network Twitter. This is a qualitative research, with data collection through literature review, documentary analysis of Brazilian legislation for education related to high school education, and discourse analysis of Twitter posts with keywords related to the new high school education. The data analysis was inspired by the theory of Laclau (2011) and Laclau and Mouffe (2015). This research was based on the perspective of social justice, with a focus on curricular justice, which involves ensuring rights such as equitable access to quality education, staying in school, and successfully completing high school as a human right linked to the right to Education (BRAZIL, 1988; 1996). The analysis of the results, based on the collected data, led to the defended thesis that the debate generated on the social network Twitter points to the expected outcome of the implementation of the new high school, as a curriculum policy, contributing to the multiplication of inequalities, widening the existing gap between private and public schools, imprisoning public schools to offer an education that generates cheap labor, deprived of rights and youth protagonism. Thus, two types of education are maintained, the propaedeutic and the one aimed at meeting market demands.
Keywords: Políticas de currículo; Novo Ensino Médio; Twitter; Teoria do discurso; Curriculum policy; New high school; Discourse theory; Políticas curriculares; Nueva escuela secundaria; Teoría del discurso; ACCNPQ::Ciências Humanas::Educação